Zambia : Using Social Safety Nets to Accelerate Poverty Reduction and Share Prosperity - Tesliuc, Cornelia; Smith, W. James; Sunkutu, Musonda Rosemary (World Bank, Washington, DC, 2014)
Despite robust annual growth of 5.7 percent in the recent past, poverty in Zambia remains stubbornly high. The poverty headcount rate is 60 percent (as of 2010), and 39 percent of the population live in extreme poverty, with insufficient consumption to meet their daily minimum food requirements. Chronic malnutrition remains very high, with 47 percent of children under the age of 5 being stunted in 2010, close to the high levels of the early 1990s. The report recommends a unified National Safety Net Program comprising cash transfers and public works to reach the poorest 20 percent of the population. The estimated cost is about US$100 million per year. This is less than 2 percent of public spending and around 15 percent of the current subsidies programs benefiting the non-poor.